PENGARUH SUHU DAN WAKTU PENYIMPANAN TERHADAP VITAMIN C DALAM JAMBU BIJI (Psidium Guajava) - masfufatun, masfufatun; Widaningsih, Widaningsih; Indahsari, Nur Kumala; Rahayuningsih, Tri (Universitas Wijaya Kusuma Surabaya, 2010)
The purpose of this study was to determine whether there is influence of temperature and storage time on vitamin C content in guava. This study is an experimental research menggunkan Completely Randomized Design (CRD) with two factors and two repetitions. Of the two factors were obtained eight combinations of treatments. Each - each treatment was repeated twice, in order to obtain 16 replicates. The parameters used were vitamin C content in guava. Guava that has been stored in a specific time and temperature peel and blend until homogeneous to obtain slurry. Furthermore slurry disentrifuge guava and filtered. Filtrate obtained its vitamin C content determined by titration method Iodometri. Data obtained with ANOVA dinalisis. If there is any real difference followed by Least Significant difference test (LSD). Results showed that storage time and temperature affect the levels of vitamin C in guava fruit ripe. The longer the storage time and the higher the temperature the lower the vitamin C content. Vitamin C content in guava stored at room temperature for 10 days decreased by 46.35% and the cold temperature is only 39%.